PHILOSOPHICAL CONCEPTUALIZATION OF SCIENCE EDUCATION AS A TOOL OF PEACEBUILDING - Denys Svyrydenko; Glib Khomenko; Yuliia Aleksandrova ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
In this paper, science education is considered as a crosscutting approach, which should be implemented at every level of education (playschools, primary and secondary schools, universities, as well as in lifelong learning). This will make it possible to radically modernize outdated forms of education. Modern education should be based primarily on research because it can protect the educational process from becoming an overt or veiled indoctrination. The training of similar characters is easily exposed to various external manipulations. This approach to education is de facto "education for war" because it doesn't contribute to the development of holistic personalities that will realize their professional and civic potential in their careers and everyday life. Science education should play a leading role in the philosophy of education for peace offering new style of communication between lecturer (teacher) and student (pupil), as well as an atypical attitude to knowledge, encouraging freedom of knowledge and creativity in the educational process.